Pengaruh Penambahan Bottom Ash Dan Fly Ash Sebagai Bahan Subtitusi Campuran Beton - Harjunan, Harjunan; Lakawa, Irwan; Hujiyanto, Hujiyanto; Ilham, Vickky Anggara (Universitas Sulawesi Tenggara, 2023)
The development of construction development is currently experiencing rapid progress, which has led to an increase in demand for construction materials. Therefore, other materials are needed as or at least materials capable of reducing the use of aggregate for use in making concrete. This effort is an alternative to utilizing waste from the agricultural plantation industry or factory waste that is left alone. The aim of this research is to analyze the characteristics and compressive strength of concrete with bottom ash as a fine aggregate additive and fly ash as an additive to cement. The location for the concrete making research was carried out at the UPTD Construction Laboratory of the water resources and community development service of the Southeast Sulawesi provincial government. With a total of 16 test objects, they were printed in a cylindrical shape with dimensions of 30 x 15 cm. Based on compressive strength testing with an f'c quality plan of 20 MPa, with 10% substitution of fly ash as cement and bottom ash as fine aggregate with variations of 10%, 15%, 20%, the compressive strength decreased. for 7 days of age respectively, it is 12.31 MPa, 11.89 MPa, and 11.46 MPa. Meanwhile, at the age of 28 days, respectively, it was 19.11 MPa, 16.99 MPa and 15.29 Mpa